Digital skills and intention to use digital health care and social welfare services among socially marginalized individuals in Finland: A cross-sectional study - Birgitta Tetri; Teemu Rantanen; Anne Kouvonen (Finnish Social and Health Informatics Association, 2024)
This article examines the relationship between digital proficiency, trust in service providers, and the intention to use digital health care and social welfare services among prisoners and people with mental health conditions in Finland. Based on cross-sectional data, which includes responses from 225 prisoners and 120 people with mental health conditions between September 2020 and May 2021, a study utilizing latent profile analysis (LPA) reveals that although high digital skills were observed, trust in providers of digital services within the health care and social welfare sector remained low, particularly among younger participants. Despite trust issues, the intention to use digital services remained high, particularly among inmates. This suggests that trust is not the sole factor influencing digital service adoption; age and perceived digital competence also play significant roles. Prisoners demonstrated higher levels of advanced internet skills than individuals with mental health backgrounds, possibly due to overestimating their abilities. Alternative approaches, such as social support and hands-on learning, are vital for enhancing digital skills in socially marginalized groups. Understanding these determinants can guide policymakers and practitioners in developing targeted interventions to promote digital inclusion effectively by considering broadly the factors that promote the accessibility of digital health care and social welfare services. Future research combining objective proficiency testing and self-reported data can offer deeper insights for more successful strategies.